ANALISA FAKTOR K3 DAN ERGONOMI TERHADAP FASILITAS PUSAT KESEHATAN UNIVERSITAS UNTUK MENGUKUR KEPUASAN PASIEN - Rio Yuwono; Ferida Yuamita (Jurnal Ilmiah Teknik Industri, 2015)
Hospitals and clinics are included in the criteria of work places with a variety of hazards that can cause health effects, not only for the employees who work in that place, but also  the patients and visitors of hospitals and clinics. With the application of K3 and ergonomics in any existing facilities in the area of the UMP clinic will result in improvement of service quality, and patient satisfaction.  The methods used in this research are Customer Satisfaction Index (CSI) and the Kano Method. The result shows that the percentage of Customer Satisfaction Index (CSI) is 59.8%, it means that the patients satisfied to the facilities and services. Based on the KANO methods, the following attributes have to improved to increase the customer satisfaction, that are the room temperature, the room tranquility, and lighting conditions.